2017
DOI: 10.1016/j.tjem.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab, a new immunomodulatory drug, a new adverse effect; adrenal crisis

Abstract: Owing to the advancements in medicine, new information is obtained regarding cancer, new antineoplastic agents are developed. Frequent use of these new pharmacological agents emergency physicians to be vigilant about their side effects. We present a case of adrenal crisis in a patient with non-small cell lung cancer (NSCLC), caused by an immunomodulatory drug; nivolumab. While adverse events are related to other immunomodulatory drugs have been reported in literature, our case is the first nivolumab-related ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Two cases of diabetes were also controlled with insulin therapy. One report described life-threatening adrenal crisis following nivolumab treatment [45].…”
Section: Nature Of Iraesmentioning
confidence: 99%
“…Two cases of diabetes were also controlled with insulin therapy. One report described life-threatening adrenal crisis following nivolumab treatment [45].…”
Section: Nature Of Iraesmentioning
confidence: 99%
“…In phase I human studies, skin (20%), gastrointestinal (15%), and pulmonary (9%) toxicities were observed, while in the phase II studies skin (31%), rash (12%), pruritus (9%), vitiligo (3%), gastrointestinal (11%), and pulmonary (3%) were reported. In general, toxicities with anti-PD-1 antibodies appear to be less common and less severe when compared with anti-CTLA-4 monoclonal antibodies [8,9,10]. Dermatologic toxicity is the most common immune-related adverse event associated with checkpoint inhibitors which is usually seen 3-4 weeks after the initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea/colitis is the most common gastrointestinal symptom presenting approximately 6-8 weeks after the commencement of therapy. [2,8,9,10,11] Boike et al have previously reported endoscopic and histopathological features of esophagitis related to Nivolumab therapy. [2] They noted marked intraepithelial T-cell lymphocytic infiltrates with dyskeratotic keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer patients on ICI therapy (e.g., ipilimumab and nivolumab) are a novel patient group in whom AC should always be considered, as it may cause severe hypophysitis or adrenalitis. 142 Moreover, several medications interact with steroid metabolism, and can cause AC, including antiepileptic drugs, barbiturates, etomidate, antituberculosis, and antifungal drugs (fluconazole, ketoconazole, voriconazole). Patients with undiagnosed hypoadrenalism can also precipitate an AC in the context of thyrotoxicosis or after the start of thyroxine therapy.…”
Section: Adrenal Crisismentioning
confidence: 99%